ANALYSIS OF STROKE RISK FACTORS ON THE FREQUENCY OF RECURRENT STROKE EVENTS IN ACUTE ISCHEMIC STROKE PATIENTS - Kurniawati, Nita; Supit, Paulus Alexander; Erwin, Ferdinand (JURNAL WIDYA MEDIKA, 2024)
Introduction: Ischemic strokes making up over three quarters of all cases are a major global cause of disability and mortality. Survivors face a 15% risk of recurrence within two years, with recurrent strokes often resulting in more severe neurological damage and increasing the risk of death and long-term disability. Methods: This retrospective cross-sectional study analyzed medical records from Gotong Royong Hospital in Surabaya from January 2023 to June 2024, selecting patients with acute ischemic stroke and a history of prior strokes. The data were descriptively analyzed and further examined using bivariate analysis to identify correlations with recurrent stroke episodes, followed by a multivariate regression analysis. Results: The study recruited 87 participants, predominantly male (64.4%), with an average age of 63.2 years and varying medical histories, including hypertension (79.3%), diabetes mellitus (46%), and dyslipidemia (31%). Bivariate analysis revealed no significant correlations between hyperten